"Political" Islam in Senegal and Burkina Faso: contrasting approaches to mobilization since the 1990s. Issue 1 (2nd January 2017) - Gomez-Perez, Muriel
Abstract: This article compares the strategies devised by two Salafi-oriented Islamic associations, the Senegal's Jamaatou Ibadou Rahmane (JIR) and the Burkina Faso's Mouvement Sunnite (MS). Drawing on extensive field research conducted between 2002 and 2013, it shows that both organizations have been engaged since the 1970s in a similar legitimacy-building process, using contrasting strategies. The JIR intends to build a more constructive relationship with the State and the brotherhoods, while still continuing to cast a critical eye on these two groups. In Burkina Faso, recurring leadership crises and violent incidents has sapped a great deal of the MS's energy. It therefore has to regain visibility and legitimacy by maintaining a certain distance from political debates. The comparison shows that political Islam has entered in both countries a transitional phase that took into account the emergence and perhaps even the consolidation of a cultural and religious form of citizenship.